Konsep kearifan lokal perspektif Al-Qur’an dan teori sosial - Al-Arzaq, Moch Nuzulutthoriq; Farhan, Ahmad Ali; Widad, Faizatul (Maliki Interdisciplinary Journal, 2024)
This article examines the concept of local wisdom from the perspectives of the Qur'an and social theory. Local wisdom refers to the knowledge, values, and practices passed down through generations within a community, playing a crucial role in the social, economic, and cultural life of society. Using an interdisciplinary approach, this study aims to understand how the Qur'an articulates and supports local wisdom and how modern social theory can enrich our understanding of this phenomenon. The findings show that the Qur'an acknowledges the importance of local values that align with Islamic principles such as justice, welfare, and social harmony. Meanwhile, social theory provides an analytical framework for understanding the dynamics of local wisdom in the context of social change and globalization.